PEMBAHARUAN PENDIDIKAN ISLAM KH. SYAFI'I HADZAMI - Burhan Burhan (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2023)
This research describes movement of educational renewal carried out by  KH. Syafi'i Hadzami is trying to develop all students as optimally as possible. Islamic education seeks to lead students towards personal maturity plenary, namely people of faith and knowledge. The role of ulama in contributing to the world of Islamic education very influences the color of education which is reflected in the educational process in Indonesia. KH. Syafi'i Hadzami is one of the scholars and educators who plays a role in advancing Islamic education in Indonesia in general and especially in the Jakarta area. The legacy of the Education system built by KH. Syafi'i Hadzami can still be seen today, with the various educational institutions he has established. The method used in this study is a qualitative method. Data collection techniques by collecting written sources obtained from text books in the library, as well as other sources that support research on KH thinking. KH. Syafi'i Hadzami on the thought of educational renewal. The results showed that educational thinking is ideal according to KH. Syafi'i Hadzami is to be in harmony with the concept of Islam. This is in accordance with the environmental and personal pattern of him as a conceptor as well as an educational practitioner. teaching methods that are often used by KH. Syafi'i Hadzami is a talqin method, assignment, discussion, exemplary, and most importantly a method of guidance and example. The exemplary method is a method that is very attached to him as a scholar. So that the method he formulated is still very relevant in its use today. So that it can be one of the references for an educator in applying the educational methods he uses in the education process today. In other words, it can be said that both conceptually and practically, that Islamic education can be flexible and contribute positively along with urbanism and cosmopolitanism and the transformation of society